Paremias in the work of Ricardo Palma - Trauco Ortega, Manuel Gabriel (2021)
This article will analyse the translations that have been made of the paremias in three stories written by Ricardo Palma. The purpose of this work is to find out how the presence of nineteenth-century Spanish and the extensive use of paremias in the work have come to hinder the understanding of the original message. My interest in the subject arises because I am studying Translation and Interpreting and I know that the effectiveness of reading comprehension is established by avoiding any kind of communicative interference such as unfamiliarity with codes.